Insulin-like growth factor II supply modifies growth of intestinal adenoma in Apc(Min/+) mice. - Hassan, A; Howell, J (2000)
Insulin-like growth factor-II (IGF-II) is an embryonic growth promoter and cell survival factor. IGF-II supply is normally limited by gene expression because transcription occurs predominantly from the paternal allele in mouse and man (maternal imprinting). Excess IGF-II has detrimental systemic and local effects in vivo, promoting somatic overgrowth and an increased frequency of tumors. IGF2 mRNA is overexpressed in colorectal and many other human cancers. In this paper, we show that altered IGF-II supply modifies intestinal tumor growth. Mice genetically altered in the IGF-II system were combined in crosses with ApcMin/+, a murine model of human familial adenomatous polyposis. Depending on genetic background, ApcMin/+ acquires multiple small intestinal adenoma before becoming moribund with anemia. Mice that express excess IGF-II delivered using a bovine keratin 10 promoter (k10Igf2/+) develop a disproportionate overgrowth of colon, uterus, and skin. Combination with ApcMin/+ leads to a 10-fold increase in the number and the diameter of colon adenoma (P<0.0001) compared to ApcMin/+ littermate controls (postnatal day 80), an increased susceptibility to rectal prolapse (41%), and a histological progression to carcinoma. Mice with reduced IGF-II supply, secondary to the disruption of the paternal Igf2 allele (Igf2+m/-p), are 60% the weight of wild-type littermates. Combination with ApcMin/+ leads to a 3-fold reduction in small intestinal adenoma number (P<0.0001) compared to ApcMin/+ littermate controls (postnatal day 150), and a significant decrease in adenoma diameter (P<0.001). With in situ hybridization, we show that Igf2 was expressed in all adenoma irrespective of IGF-II supply. This suggests that there is an increased maternal allele expression of Igf2 (loss of imprinting) in adenoma which form, despite paternal Igf2 allele disruption. We conclude that IGF-II supply is a modifier of intestinal adenoma growth, and we provide genetic evidence for its functional role in colorectal cancer progression.